Lexical Errors in English Language Writing – The Case of selected Senior High School students in the Ashanti Region of Ghana - Dorah Mensah; Charles Owu-Ewie; Levina Nyameye Abunya; Albert Abban; Halimatu Sadia Jibril (E-Journal of Humanities, Arts and Social Sciences)
The present study analyses the lexical errors committed by students in their written output. Using the Quantitative approach, it examines the lexical errors of students selected from each of the three-layered categories (A, B, and C) of Senior High schools in the Ashanti Region of Ghana. A sample of 824 out of 2713 students was arrived at through Yamane’s sample size determiner. The sample was selected through the systematic random sampling strategy. A model based on Corder’s Error Analysis theory was used to analyse the data. The results revealed that the students committed lexical errors in varying frequencies. Lexical errors identified from the essays were wrong word selections, literal translation, omission, misspelling, punctuation, capitalisation, modification, collocation, and morphological/word formation errors. Punctuation errors had the highest occurrence whereas literal translation errors had the least occurrence. The findings also revealed that lexical errors in the students’ output affected clarity and hindered effective communication by causing confusion, misinterpretation, and distortion of the intended messages. The study recommends that English language teachers should employ practical teaching and error correction strategies to address the writing challenges of students. Students should keep track of their learning; identify their weaknesses and relate such to their teachers for redress.